Post-treatment effect of sodium and dodescyl sulphate-triethanolamine on the in vitro dry matter digestibility estimation of tanniferous tree leaves using polyethylene glycol-6000 - Vaithiyanathan, S; Mishra, J P; Jakhmola, R C (The Indian Journal of Animal Sciences, 2005)
The aim of the present experiment was to find out effect of sodium dodecyl sulphate (SDS)-triethanolamine (TE) addition at the end of the incubation period on in vitro dry matter digestibility (IVDMD) of young and mature leaves of tanminiferous trees (Bauhinian racemosa, Dicrostachhys nutans, Ficus bengalensis, F religiosa, Gymnosporia spinosa, Prosopis cineraria and Zizyphus mamularia) treated with polyethylene glycol (PEG)-6000. Most of young leaves had higher amount of condensed tannin (CT) (ranging from 1.03 to 13.13% DM) than in mature leaves (ranging from 0.31 to 14.0% DM). The IVDMD ranged from 25.33 to 66.27 and 18.40 to 36.47%, respectively, for young and mature leaves. CT had significantly (P<0.05) negatively (r²=-0.307) affected the IVDMD of Leaves. The change in IVDMD due to PEG 6000 treatment varied from-10.53 to 5.07 and -3.07 to 6.60 units in young leaves and mature leaves respectively. The unit change in IVDMD due to PEG-6000 was significantly (P<0.05) negatively (r²= -0.349) related to CT in leaves. The posttreatment with SDS-TE improved the IVDMD. The change in IVDMD due to PEG-6000 and SDS-TE varied from 3.73 to 14.36 units in young leaves and 0.53 to 19.13 units in mature leaves. The relationship between units change in IVDMD due to PEG-6000 and SDS-TE became significantly (P<0.05) positively related (r² =0.3 16) to CT in leaves. PEG-6000 treatment negatively affected the IVDMD in most of the tree leaves. But the post-treatment with SDS-TE showed the real iniprovement in IVDMD because of PEG-6000 treatment in all tanniniferous leaves. This technique can be used in IVDMD method for in vitro assessment of tanniniferous tree leaves using PEG-6000.